Chronic pruritus in an elderly patient with dementia successfully treated with paroxetine - Heisig, Monika; Salomon, Joanna; Szepietowski, Jacek (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . Chronic pruritus is a significant diagnostic and therapeutic challenge. Psychogenic pruritus is a variant of chronic itching and the diagnostic criteria for it have recently been established. In the therapy of psychogenic pruritus psychotropic drugs, including paroxetine, can be used. Objective . To present a patient with chronic pruritus of a psychogenic background successfully treated with paroxetine. Case report . An 80-year-old man with mild dementia was admitted to the department due to chronic pruritus. On admission the patient presented numerous secondary lesions caused by scratching which proved a very high intensity of pruritus. Therapy with antihistaminics was ineffective. Laboratory investigations did not reveal significant abnormalities. The patient fulfilled criteria for psychogenic pruritus. Therapy with paroxetine was introduced and fast improvement of intensity of pruritus and gradual improvement of skin condition were observed. Conclusions . Paroxetine is an effective drug in the therapy of psychogenic pruritus.